Partnerships as the path to stability in fragile settings - Kosec, Katrina (CGIAR, 2024)
As the humanitarian crisis deepens in Gaza, where conflict has devastated millions, the call for durable solutions has never been more urgent. This crisis, as well as escalating emergencies in Sudan, Yemen, Ethiopia, and Ukraine—among many others—underscores the critical need for effective strategies to protect, respond to, and stabilize vulnerable communities facing conflict, crises, and climate-induced disasters.